2014
DOI: 10.1038/srep07085
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous lung surfactant inspired pH responsive nanovesicle aerosols: Pulmonary compatible and site-specific drug delivery in lung metastases

Abstract: Concerns related to pulmonary toxicity and non-specificity of nanoparticles have limited their clinical applications for aerosol delivery of chemotherapeutics in lung cancer. We hypothesized that pulmonary surfactant mimetic nanoparticles that offer pH responsive release specifically in tumor may be a possible solution to overcome these issues. We therefore developed lung surfactant mimetic and pH responsive lipid nanovesicles for aerosol delivery of paclitaxel in metastatic lung cancer. 100–200 nm sized nanov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Inhaled delivery of drug-loaded nanoparticles led to lower drug concentrations in non-targeted sites (liver, spleen and plasma) compared with intravenous paclitaxel solution. Drug-loaded nanoparticles showed no lung toxicity [96] .…”
Section: Paclitaxelmentioning
confidence: 96%
See 1 more Smart Citation
“…Inhaled delivery of drug-loaded nanoparticles led to lower drug concentrations in non-targeted sites (liver, spleen and plasma) compared with intravenous paclitaxel solution. Drug-loaded nanoparticles showed no lung toxicity [96] .…”
Section: Paclitaxelmentioning
confidence: 96%
“…These nanovesicles fuse with the cell plasma membrane and lysosomal membrane at low pH, thus providing site-specific and triggered delivery of anticancer drugs to cancer cells [93][94][95] . It has been demonstrated that pulmonary surfactant mimetic pHsensitive nanoparticles are cytotoxic to lung tumor cells while being compatible with healthy lung cells, indicating a selective toxicity of the developed formulation to lung cancer cells [96] .…”
Section: Nano-carriers For Inhaled Drug Deliverymentioning
confidence: 99%
“…(27) Inhaled (IH) paclitaxel for locoregional NSCLC treatment has demonstrated proof of principle in a variety of preclinical models. (28)(29)(30)(31)(32)(33)(34)(35)(36)(37) To evaluate its potential as an IH lung cancer therapy, NanoPac suspension was administered to healthy rats through nebulized inhalation to determine the pharmacokinetic profile in both lung tissue and circulating plasma. Quantifiable levels of paclitaxel were detected in lung tissue at final necropsy, 2 weeks after single administration.…”
Section: Introductionmentioning
confidence: 99%
“…The aerosol treatment (10 ml of 0.5 mg/ml paclitaxel liposomal formulation for 5 consecutive days every week) was compared to intravenous treatment with two commercial formulations of the drug Taxol Õ and Abraxane Õ (10 mg/kg once every 3 d). The aerosol treatment showed no major pulmonary toxicities such as fibrosis and chronic inflammation and produced a significant reduction in the number of metastases and lung surface occupied by the lesions, with an overall metastases inhibition of nearly 75%, superior to the parenteral treatment with both commercial product (around 50% inhibition for both treatments) (Joshi et al, 2014).…”
Section: Nanocarrier Formulations Administered As Liquid Aerosolsmentioning
confidence: 93%